If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -43 + -1x = 87 + 4x Solving -43 + -1x = 87 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -43 + -1x + -4x = 87 + 4x + -4x Combine like terms: -1x + -4x = -5x -43 + -5x = 87 + 4x + -4x Combine like terms: 4x + -4x = 0 -43 + -5x = 87 + 0 -43 + -5x = 87 Add '43' to each side of the equation. -43 + 43 + -5x = 87 + 43 Combine like terms: -43 + 43 = 0 0 + -5x = 87 + 43 -5x = 87 + 43 Combine like terms: 87 + 43 = 130 -5x = 130 Divide each side by '-5'. x = -26 Simplifying x = -26
| 0.6(x-1.7)=18 | | 50w+400=1200 | | 7t^2+3x-3t^2= | | 50w+400=120 | | 3(x-7)=9x+27 | | 10x+2s-3x-2x= | | 2x-4(x+5)+10=4x+11 | | 275=(8x)+4(1.5X) | | 10x+2(3x+1)=1+7(2x+3) | | -3(6x-3)+2x=-3 | | -8+5v=2 | | -3(5x+8)=-4 | | (15x+8)=(21x-10) | | 20=-6w+2(w+8) | | 4(-7x+5)+4x=1 | | -6-5(7x-3)=2 | | 4x+86=11x-5 | | Y=-ctgx | | -9-3(8x+8)=13 | | 24*24=12x | | 4(x-8)+10=-8 | | 2X+4X-24=64 | | 3n+2=5n-2 | | -47+9x=33+4x | | x^2+50x-3600=0 | | 4u=u | | -7x+11+9x+19=-4 | | X^2=16+((X-4)+(X+4)) | | 8x-8-6x=4 | | -9x+15+11x-17=6 | | 2(x+3)(x-1)=0 | | 18v+20v=12 |